Development of a green-synthesized molecularly imprinted polymer-based electrochemical nanosensor for the determination of N-nitrosodimethylamine (NDMA) in serum and tap water - Jadon, Nimisha; Cetinkaya, Ahmet; Ozcelikay-Akyildiz, Goksu; Kaya, S. Irem; Atici, Esen Bellur; Uzun, Lokman; Ozkan, Sibel A. (Springer Wien, 2024)
N-nitrosodimethylamine (NDMA) was determined using a molecularly imprinted polymer (MIP)-based electrochemical sensor. Green-synthesized silver nanoparticles were functionalized with cysteamine to enhance their integration into the electrode surface, which was used to modify a glassy carbon electrode (GCE). Furthermore, a MIP-based electrochemical sensor was constructed via electropolymerization of 3-aminophenyl boronic acid (3-APBA) as a conjugated functional monomer in the presence of lithium perchlorate (LiClO4) solution as a dopant, chitosan as a carrier natural polymer, and NDMA as a template/target molecule. The polymer film was characterized by scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). The analytical performance of the silver nanomaterial-based MIP-based electrochemical (AgNPs@Chitosan/3-APBA@MIP-GCE) sensor was evaluated under optimized conditions. The linear range of NDMA was 1.0 x 10-13-1.0 x 10-12 M (0.1-1.0 pM), with a limit of detection (LOD) of 3.63 x 10-15 M (3.63 fM) using differential pulse voltammetry (DPV). Method validation figured out that the developed MIP-based electrochemical nanosensor exhibited excellent selectivity, accuracy, and precision, which was shown by the analysis of synthetic serum samples and tap water. The LOD and LOQ in serum samples were 17.8 fM and 59.5 fM, respectively, which were in agreement with the developed method. Good recovery results confirm the successful application of the method in serum and tap water samples. The selectivity of the developed AgNPs@Chitosan/3-APBA@MIP-GCE sensor for NDMA was demonstrated in the presence of NDEA, sartans (valsartan, losartan, irbesartan, candesartan, telmisartan), and potential interferents that are possibly present in biological fluids (dopamine, ascorbic acid, uric acid) besides ionic species (sodium, chloride, potassium, nitrate, magnesium, sulfate) and common analgesic paracetamol.
Keywords: Electrochemical sensor; Modified glassy carbon electrode; Differential pulse voltammetry; Electropolymerization; Green-synthesis; Molecularly imprinted polymer; Nitrosamines